Factors Affecting Weight Gain in Nelore Calves from Weaning to Marketing in the Bolivian Tropic - Atsuko, Ikeda; Figueredo Villca, Yoselin Zelma (European Journal of Applied Sciences, 2021)
The objective of the work was to evaluate the factors that affect live weight gain in the rearing stage in Nelore calves in grazing systems in the Bolivian tropics. Retrospective data corresponding to the period between 2015 and 2016 were used, corresponding to 109 weaned male calves of the Nelore breed, belonging to the Foundation Technology Center on Agriculture and Livestock in Bolivia, Santa Cruz, Bolivia. The following variables were evaluated: date of birth of the calf, live weight of the calf at birth in kg, age of the father in years, age of the mother in years, live weight of the mother in kg and live weight of the calf every 30 days until its sale slaughter in kg. The weights at birth were 38.8 ± 5 kg, at 240 days (weaning) 233.2 ± 25 kg and at 600 days (sale) 482 ± 40 kg. Live weight values ​​at 600 days according to time of birth: late 488 ± 35 kg and early 479 ± 42 kg and according to the year of birth (2015) 481 ± 42 kg and (2016) 483 ± 37 kg. There was significant interaction between the Years-Epoch and time, indicating that the average final live weight over time differs between the different Year-Epoch groups. In addition, the variable live weight at birth was also significant (p≤0.05). For the two years (2015 and 2016) and the 4 seasons (early and late 2015; early and late 2016), the final weight increases 2.28 kg for each unit increase in live weight at birth. The live weight at birth, the years and times were shown to be the factors affecting the increase in live weight in the rearing stage in the Bolivian tropics.